中国奇女子：论褚松雪的女性主义和其作品 = Chinese female hero: the feminism of SongXue Chu and her literature appreciation - 黄隽凯 Wong, Chun Hoi (Nanyang Technological University, 2025)
褚松雪（1896-1995）以其独特的经历和非凡的才华，成为了20世纪初中国文学以及政治舞台上的传奇人物。然而关于褚松雪的研究往往是建立于对其丈夫，亦是中国性学研究第一人张竞生，是作为研究旁枝而存在的。 因此，笔者希望通过回顾褚松雪的生平以及其主要作品，强调其在中国文学史上以独特的女性主义色彩以及婚姻自主方面的前卫风格解析，通过细读《花落春犹在》、《离婚问题》以及《我的性历史》等著作，从而探讨褚松雪作品中的女性主义思想，性别关系的复杂性以及其对传统社会的挑战。 通过对褚松雪作品的细读，本论文发现其不仅以先锋的女性主义视角探讨婚姻与性别议题，其作品突破了传统道德束缚，展示了女性在婚姻选择、情感自助与性关系中的复杂性。本论文不仅填补了对褚松雪个体及其作品系统性分析的空白，同时深化了对20世纪初期中国女性主义文学的理解，以考察中国女性主义文学中婚姻、性别议题等演变。SongXue Chu (1896-1995) is one of the legendary iconic female characters in the earliest century of China literary community, as well as political arena. However, studies on Chu often revolve around her ex-husband, Jing Sheng Zhang, who is regarded as the first figure of Chinese Sexology, and thus studies on her are frequently treated as a secondary subject. In this research, the author would like to highlight Chu’s unique feminist perspective and avant-garde approach to martial autonomy in Chinese literature. By closely analyzing her key works, to explore the feminist themes, complexities of gender relationships as well as challenges to traditional society present in her writing. Ultimately, this research highlights Chu’s pioneering feminist perspective on marriage and gender issue, challenging traditional norms and revealing the complexities of female agency. It fills a gap in the study of her literature while deepening the understanding of early 20th-century Chinese feminist discourse.